Use Chest Vibrator to Prevent Pulmonary Infection in Patients with COPD - Luthfiyah, Sari; Utomo, Bedjo; Ariswati, Her Gumiwang (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2019)
Chest infection is an infection that affects your lungs, either in the major respiratory tract (bronchitis) or in small air sacs (pneumonia). There is an accumulation of pus and liquid (mucus), and the respiratory tract becomes swollen, making breathing difficult. Chronic obstructive pulmonary disease (COPD) is a serious cause of death globally. This disease is characterized by episodes of acute exacerbations or aggravation that are superimposed upon a gradual decrease in pulmonary function. The study developed a device for vibratory techniques in chest physiotherapy. Vibration is a pressure applied to the chest during exhalation to move the secret into the large respiratory tract. Measurements of the mechanical impedance of the respiratory system in frequencies from about 5 Hz to about 70 Hz in the higher frequency range should be evaluated on the basis of the lung model. In this device, using frequencies that are often used in the field: 30, 40, 50 Hz and a timer of 3 to 5 minutes. This device uses a 12V DC motor as a vibration medium that will be connected to the engine inside the paddle. It uses IC NE 555 as an important component of the conductor circuit. This module uses an LCD screen of 16x2 characters as screen. The result was found that by using IC NE 555 as an important driver in showing acceptable system accuracy, only a minimum error value of ± 0.008% and a maximum error value of ± 0.02%. The advantage of this module is that it is equipped with a 3-5 minutes timer so that it can provide efficient therapy according to the time needed and is equipped with an LCD display to make it easier to observe the time